Warehousing and transportation logistics of mango in Colombia: A system dynamics model - Orjuela-Castro, Javier Arturo; Herrera-Ramírez, Milton Mauricio; Adarme-Jaimes, Wilson (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper evaluates the incidence of packing asymmetries, resulted from the use of heterogeneous packaging materials by different mango supply chain actors in Colombia, on performance measures of inventory, transportation, and quality. A system dynamics model was proposed based on the literature review on inventory and transportation logistics, the studies on asymmetries in supply chain, packing, and packaging, and the results of the characterization of the fruit chain logistics in various departments of Colombia from 2012 to 2013. We used the proposed model to test the following hypothesis: “The asymmetry in the packaging, derived from the actors’ individual management, creates inefficiencies that may be avoid if the packaging of the fruit is done thinking on the chain”. The developed simulation model allowed us to prove the proposed dynamic hypothesis. Forrester’s model includes four echelons for the supply chain: production, processing, wholesale, and retail, as well as warehousing, transportation and information.